Thermal comfort in urban green areas:: simulation of the microclimate in Liberty Square, in Teresina-PI - Leal Melo de Oliveira, Ylana (2021)
Features of the built environment lead to changes in the microclimate and might contribute to the urban heat islands effect (UHI). The use of bioclimatic strategies to mitigate UHI effects is essential for urban planning. In this sense, green areas contribute to sustain climate patterns and enhance quality of life. This study aims to describe a microclimate performance sample at Liberty Square, in Teresina-PI, in the dry and wet seasons. This study aimed to understand the influence of the vegetation and its surroundings in the quality of the urban green spaces. The microclimate analysis was conducted through computational simulation, with the ENVI-met V.4.4.5. software and it was divided into four methodological steps: data collection, modeling, simulation, and results extraction. Results indicate the incidence of high temperatures in both seasons, and the afternoon being the most critical time in both scenarios; however, the wet season showed better rates of thermal comfort, with differences of up to 2.72ºC in the hottest time. Similarly, better rates of comfort were measured under the trees in both seasons of the year. Regarding the PMV, the study area does not offer sense of thermal comfort in both seasons, going from “mild heat” to “very hot”.